(untitled) (Research, Society and Development, 2022)
The challenges experienced by multiprofessional residents in the face of palliative sedation, and the need for training to train ethical, humane and reflective professionals in palliative care are impasses that directly reflect on patient care. The objective of this present work is to discuss the perception of multiprofessional residents in the face of oncological palliative sedation based on an analysis of scientific articles on the subject. This is an integrative review including primary articles indexed in the LILACS, MEDLINE, BDENF, IBECS and COLECIONA SUS databases, as recommended by the PRISMA tool, published from 2017 onwards. After analysis, it was observed that the publications involved related aspects, categorizing 03 main themes: Bioethical perception of residents on palliative sedation; perception of good practices in palliative sedation and perception of residents’ professional training on palliative sedation. A large gap in the topic addressed was identified. All these aspects have a direct impact on the performance of residents in the process of approaching oncological palliative sedation due to insecurity and unpreparedness, making it necessary to approach the topic in the training of these professionals.